Patient satisfaction with pharmacy services and associated factors in Ethiopia: a systematic review and meta-analysis - Sisay Molla; Getachew Moges; Husien Nurahmed Toleha; Ewunetie Mekashaw Bayked; Birhanu Demeke Workneh (BMC Health Services Research)
Abstract Introduction Patient satisfaction reflects the discrepancy between anticipated and actual healthcare service delivery, serving as a pivotal metric for strategic healthcare decision-making. This systematic review and meta-analysis aimed to assess the magnitude of patient satisfaction with pharmacy services and its determinants in Ethiopia. Methods A systematic search was performed across multiple electronic databases, including PubMed, Hinari, Semantic Scholar, EMBASE, Scopus, Web of Science, and Google Scholar, to identify both published and unpublished relevant studies. Methodological quality and risk of bias were assessed using the Joanna Briggs Institute (JBI) critical appraisal tools and in accordance with the PRISMA 2020 guidelines. Statistical analyses were conducted using Stata version 17. Results In total, 19 articles were included in the qualitative synthesis, of which 11 were selected for the quantitative analysis. The pooled prevalence of patient satisfaction with pharmacy services in Ethiopia was 56% (95% CI: 50–62), with significant associations observed with sociodemographic, socioeconomic, provider communication, and healthcare facility-related factors. Conclusion Approximately 40% of patients expressed dissatisfaction with pharmacy services, underscoring significant systemic deficiencies. To improve healthcare quality, policymakers and healthcare administrators should prioritize the optimization of pharmacy service delivery by implementing evidence-based interventions targeting the key contributing factors identified in this study.